2014
DOI: 10.1080/17597269.2015.1024387
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the hydrodynamic performance of carbonation sumps in High Rate Algal Pond (HRAP)raceways using computational fluid dynamics (CFD)

Abstract: The production of microalgae requires carbonation and deoxygenation which is commonly supplied through a sump. This needs to be designed to minimise the energy loss to ensure a high net energy gain from the biofuel. Computational fluid dynamics was used to evaluate different sump designs and flow velocities in terms of energy loss and flow distribution to find the optimum configuration. It was established that increasing the radius of curvature of the corners to 0.1 m and the implantation of one flow deflector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…The crater curvature should match the path of the blades, thus reducing leakage. Specific studies have shown that an optimal design of the paddlewheel can increase the efficiency from 10% to 60% (Musgrove, Heaven and Muller, 2017). According to these considerations, the paddlewheels of the HRAPs presented in this manuscript were designed with 8 aluminium paddles, a gap of 2.5 cm between the paddles and the floor, and a crater of 10 cm depth and 1 m length.…”
Section: T}mentioning
confidence: 99%
See 1 more Smart Citation
“…The crater curvature should match the path of the blades, thus reducing leakage. Specific studies have shown that an optimal design of the paddlewheel can increase the efficiency from 10% to 60% (Musgrove, Heaven and Muller, 2017). According to these considerations, the paddlewheels of the HRAPs presented in this manuscript were designed with 8 aluminium paddles, a gap of 2.5 cm between the paddles and the floor, and a crater of 10 cm depth and 1 m length.…”
Section: T}mentioning
confidence: 99%
“…6.5) only refers to the energy needed for water flow, but not to the engine consumption, the type of wheel and the gearbox used, which are directly related to energy consumption. (Musgrove et al, 2017) reported that the total power required can be 5 times the calculated hydraulic power, which should be taken into account for the selection of the corresponding engines. The parameters used for the hydraulic sizing are shown in Table 6.3.…”
mentioning
confidence: 99%